Peran Laporan Keberlanjutan, Green Accounting, Kepemilikan Manajerial pada Nilai Perusahaan - Ayu Luthfiyah Ramadhanti; Nera Marinda Machdar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Firm value is investors' perception of the company's success rate, which is often associated with profitability. Firm value is influenced by many things such as sustainability reports, green accounting, and managerial ownership. The purpose of this study was to determine and analyze the effect of sustainability reports, green accounting, and managerial ownership on firm value and, to determine and analyze profitability as a moderating variable able to strengthen the relationship between sustainability reports, green accounting, and managerial ownership on firm value. This type of research uses causal research with quantitative data. The population used in this study were all mining companies listed on the Indonesia Stock Exchange during the 2019-2024 period. The samples used in this study were 63 mining companies. The sampling method uses purposive sampling with predetermined criteria. Using annual reports with a time span of 2019-2024. The analysis method used is multiple linear regression analysis. Future research can include other sectors besides mining in its data, so that research is expected to provide generalizable results for all companies in Indonesia.